2021
DOI: 10.3389/fmicb.2021.675665
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Factors on the Variability of Archaeal Communities in a Karst Wetland

Abstract: Archaea are ubiquitous and play an important role in elemental cycles in Earth’s biosphere; but little is known about their diversity, distribution, abundance, and impact in karst environments. The present study investigated the effect of environmental factors on the variability of archaeal communities in the sediment of the Huixian karst wetland, the largest karst wetland in South China. Sediment cores were obtained from four sampling sites with different water depths and macrophyte inhabitants in both the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…In this system, the relative abundance of MCG archaea was second only to Euryarchaeota and Thaumarchaeota. MCG archaea were the most widely distributed class of uncultured archaea, widely present in marine, soil, and low-temperature environments [36]. Some scholars have also found MCG archaea in biogas fermentation systems; Yuan et al [37] detected MCG archaea in a mixed biogas fermentation system of corn straw and pig manure, and Chen [38] found them in an anaerobic bioreactor treating animal manure; Wilkins et al [39] found MCG archaea in a biological treatment reactor for beverage plant wastewater with abundance second only to methanogens.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, the relative abundance of MCG archaea was second only to Euryarchaeota and Thaumarchaeota. MCG archaea were the most widely distributed class of uncultured archaea, widely present in marine, soil, and low-temperature environments [36]. Some scholars have also found MCG archaea in biogas fermentation systems; Yuan et al [37] detected MCG archaea in a mixed biogas fermentation system of corn straw and pig manure, and Chen [38] found them in an anaerobic bioreactor treating animal manure; Wilkins et al [39] found MCG archaea in a biological treatment reactor for beverage plant wastewater with abundance second only to methanogens.…”
Section: Discussionmentioning
confidence: 99%